2021
DOI: 10.48550/arxiv.2110.06040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Teleportation-based noiseless quantum amplification of coherent states of light

Jaromír Fiurášek

Abstract: We propose and theoretically analyze a teleportation-based scheme for high-fidelity noiseless quantum amplification of coherent states of light. In our approach, the probabilistic noiseless quantum amplification operation is encoded into a suitable auxiliary two-mode entangled state and then applied to the input coherent state via continuous-variable quantum teleportation. The scheme requires conditioning on the outcomes of homodyne measurements in the teleportation protocol. In contrast to high-fidelity noise… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…Finally, we showed that a distributed n-QS quantum relay is loss-tolerant with fast rates, hence is useful as building blocks for quantum repeater networks. Note added.-The authors recently became aware of a new related work which investigated noiseless quantum tele-amplifiers from a different angle [52], based on the continuous-variable teleportation protocol [35].…”
mentioning
confidence: 99%
“…Finally, we showed that a distributed n-QS quantum relay is loss-tolerant with fast rates, hence is useful as building blocks for quantum repeater networks. Note added.-The authors recently became aware of a new related work which investigated noiseless quantum tele-amplifiers from a different angle [52], based on the continuous-variable teleportation protocol [35].…”
mentioning
confidence: 99%